2012
DOI: 10.4238/2012.september.20.1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation based on microsatellite analysis of the oriental river prawn, Macrobrachium nipponense from Qiandao Lake in China

Abstract: ABSTRACT. The oriental river prawn (Macrobrachium nipponense) is an important freshwater prawn species in China. We collected 236 oriental river prawns from four wild stocks from Qiandao Lake, Zhejiang, China, and used nine polymorphic microsatellite markers to investigate their genetic diversity and structure, to facilitate the development of a selective breeding program. We found 185 alleles at nine loci in this sample. The observed heterozygosity (H O ) and expected heterozygosity (H E ) ranged from 0.43 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…Microsatellites are codominant, highly polymorphic, and ideal for genetic diversity, population structure and genetic mapping studies (Ma et al, 2012;Liu et al, 2013). A few microsatellites are available for C. alburnus (Chen et al, 2009;Li et al, 2010;Qi et al, 2013 ), but unfortunately, the number of SSRs available for this species is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Microsatellites are codominant, highly polymorphic, and ideal for genetic diversity, population structure and genetic mapping studies (Ma et al, 2012;Liu et al, 2013). A few microsatellites are available for C. alburnus (Chen et al, 2009;Li et al, 2010;Qi et al, 2013 ), but unfortunately, the number of SSRs available for this species is limited.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, F ST values were 0.029-0.143, which is high compared with other fishery species (Li et al, 2006;Zhan et al, 2008;Ma et al, 2012). Long periods of geographical and ecological isolation, in addition to random mating within the natural habitat, may explain the genetic differentiation of M. meretrix (Lin, 2007).…”
Section: Molecular Distinction and Relationships Among The 5 Populationsmentioning
confidence: 54%
“…The quality of offspring is mainly determined by additive genetic factors (Liu and Cordes, 2004). Highly abundant genetic variation contributes to the survival of populations as an adaptation to environmental change (Ma et al, 2012). In this study, the SD and JS populations showed the least variation.…”
Section: Molecular Distinction and Relationships Among The 5 Populationsmentioning
confidence: 59%
See 2 more Smart Citations